2011
DOI: 10.1166/jctn.2011.1871
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Gun Composed of Carbon Nanotube

Abstract: Using molecular simulation, this paper predicts that by bending one end of the outer carbon nanotube (CNT) of a double-wall CNT (DWCNT), the inner CNT could possibly be shot out with a speed of several 100 m/s, and a kinetic energy of several eV from either left or the right end of the outer CNT, depending on the length of inner CNT. Analysis in this paper suggests that the outer CNT is a supplier of the CNT bullet's kinetic energy and the bullet can be shot out only if the outer CNT buckles while the inner CN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…There are a number of different approaches that may be used to realize nanoscale mass transport 2-15 based on CNT nanoelectromechanical systems (NEMS). The experimental approaches include electrophoretic, 2-6 thermophoretic, [7][8][9] and mechanically actuated [10][11][12][13][14][15] methods. Electrophoretic methods can cause the motion of metal clusters [2][3][4][5] or bio-molecules 6 controlled by an external electric field.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of different approaches that may be used to realize nanoscale mass transport 2-15 based on CNT nanoelectromechanical systems (NEMS). The experimental approaches include electrophoretic, 2-6 thermophoretic, [7][8][9] and mechanically actuated [10][11][12][13][14][15] methods. Electrophoretic methods can cause the motion of metal clusters [2][3][4][5] or bio-molecules 6 controlled by an external electric field.…”
mentioning
confidence: 99%
“…Chang et al 10 proposed a mechanism to shoot out a C 60 molecule by stimulating a domino wave on a thick single-walled carbon nanotube (SWNT). Hu et al 11 and Kan et al 12 performed molecular dynamic simulations (MDS) of the transport of atomic mass driven by the bending of a CNT. Chen et al 13 and Qiu et al 14 further demonstrated that an excited vibrating CNT cantilever can act as an efficient and simple nanopump.…”
mentioning
confidence: 99%
“…[1][2][3] This goal was partially realized by the scanning tunnelling microscope (STM) with its ability to manipulate atoms on the surface of a metal. There are a number of different approaches to nanoscale mass transport [7][8][9][10][11][12][13][14][15][16] based on carbon nanotube (CNT) nanoelectromechanical systems (NEMS) that attempt to exhibit promising properties of the CNT. The experimental approaches include electrophoretic, 7-9 thermophoretic, 10,11 and mechanically actuated [12][13][14][15][16] methods.…”
mentioning
confidence: 99%